2011
DOI: 10.2298/mpns1112583m
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenems resistance of Acinetobacter spp strains isolated from wound swabs during 2009-2010

Abstract: Our results show high resistance to carbapenems in Acinetobacter spp strains isolated from wound swabs. These facts suggest the need for continuous monitoring of susceptibility in order to take adequate measures to prevent and control spreading of resistant strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Immunocompromised patients are particularly susceptible. Studies conducted in Bulgaria and Korea confirmed susceptibility of Acinetobacter to colistin, which was also the case in the presented patient 17 . Survival rates in such patients after 1-and 3-year therapy range from 50% and 25%, respectively 9 .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Immunocompromised patients are particularly susceptible. Studies conducted in Bulgaria and Korea confirmed susceptibility of Acinetobacter to colistin, which was also the case in the presented patient 17 . Survival rates in such patients after 1-and 3-year therapy range from 50% and 25%, respectively 9 .…”
Section: Discussionsupporting
confidence: 82%
“…Gram-negative peritonitis is particularly troublesome and severe resulting mostly in technique failure, catheter removal or even lethal out- come 5,6 . The increased incidence of multiresistant strains of Acinetobacter has been reported in Serbia as well as in Italy, Greece, Slovakia, China and USA 16,17 . Multiple myeloma is a disease characterised by a high incidence of severe complications, especially when renal function is disturbed and patients are subjected to any of dialysis methods (HD or PD) 7,8 .…”
Section: Discussionmentioning
confidence: 99%
“…Differences between resistance rates among non‐fermenters from 8% to 34% to beta‐lactam/inhibitor combinations, 19–74% to fluoroquinolones, 17–74% to carbapenems and 3–82% to aminoglycosides were seen worldwide . Reports published in Serbia also show a high prevalence of carbapenem resistance (36–80%) among non‐fermenters …”
Section: Resultsmentioning
confidence: 99%
“…The resistance of Acinetobacter baumannii to carbapenems, mostly to imipenem, has been the topic of various papers, and the published data on the resistance rates to imipenem have reported from 21% up to 100% of the tested isolates of A. baumannii (15, 16, 17). Among the European countries the resistance rates to carbapenems are highest in the countries in southern Europe, such as Greece and Croatia (14, 19). …”
Section: Discussionmentioning
confidence: 99%
“…Medic et al found that the resistance to cephalosporins third and fourth generations as well as ciprofloxacin was greater than 93% (19). Acinetobacter baumannii isolates are often susceptible only to colistin or tigecycline.…”
Section: Discussionmentioning
confidence: 99%